HUBUNGAN SIFAT KUANTITATIF DAN REPRODUKSI SAPI PERANAKAN ONGOLE DI KABUPATEN REMBANG - Indahwati, Ahyuni; Kurnianto, Edy; Setiatin , Enny Tantini; Samsudewa, Daud (Jurnal Sain Peternakan Indonesia, 2024)
This study aimed to analyze the relationship between quantitative traits and reproduction traits of Ongole grade cows in Rembang Regency. This study was done from May to July 2022. The number of samples used was 224 Ongole grade cows that have given birth at least once. Quantitative traits were obtained by measuring body condition scores (BCS), body length (BL), body height (BH) and chest circumference (CC). The class was based on Indonesian National Standards for Ongole grade cow breeding cattle in 2015 (Class I, II, III and Non-Class). The BCS used is the American system for beef cattle (score 1 to 9). The BL and BH were measured with a measurement stick. The CC was measured using the weight body Round-O (WB Round-O). The reproductive traits measured included service per conception (S/C), calving interval (CI), days open (DO) and estrus postpartum (EPP), which were obtained by observing cattle and interviewing breeders and inseminators. The analysis used was descriptive statistical analysis with averages and percentages and non-parametric analysis of Spearman’s correlation test.  This research concludes a significant relationship between quantitative traits and S/C with a very weak negative direction and strength of the relationship.